A hierarchical Co3O4/CoS microbox heterostructure as a highly efficient bifunctional electrocatalyst for rechargeable Zn–air batteries. Issue 32 (5th August 2021) - Min, Kyeongseok; Kim, Sangjin; Lee, Eoyoon; Yoo, Geunsang; Ham, Hyung Chul; Shim, Sang Eun; Lim, Dongwook; Baeck, Sung-Hyeon
Abstract : A hierarchical Co3 O4 /CoS catalyst derived from a Prussian blue analog (PBA) shows high cell voltage, outstanding power density, and remarkable cycling stability when used in a rechargeable Zn–air battery. Abstract : Herein, we report the synthesis of a strongly coupled Co3 O4 /CoS microbox heterostructure, prepared through an annealing treatment with the subsequent hydrothermal sulfidation of a Co–Co Prussian blue analog (PBA) precursor. The unique 3D hierarchical architecture and potential synergies of Co3 O4 and CoS provide benefits to the Co3 O4 /CoS heterostructure for both oxygen reduction and evolution reactions (ORR and OER). It displays comparable ORR catalytic activity (half-wave potential of 0.820 V) to state-of-the-art Pt/C but better durability and methanol tolerance. The Co3 O4 /CoS electrocatalyst also shows high OER activity with a relatively low overpotential (349 mV at 10 mA cm −2 ) and small Tafel slope (66.6 mV dec −1 ), compared to those of commercial RuO2 (366 mV at 10 mA cm −2 and 86.3 mV dec −1, respectively), making it a potential bifunctional electrocatalyst for both the ORR and the OER. Moreover, a rechargeable Zn–air battery with a Co3 O4 /CoS cathode shows a higher cell voltage (1.51 V), higher power density (168 mW cm −2 at 269 mA cm −2 ), and better cycling stability (up to 150 cycles) than the same battery with the state-of-the-art Pt/C + RuO2 catalyst. This PBA-based material with a strongly coupled interface between Co3 O4 and CoS offers insights into the development of low-cost and highly efficient electrocatalysts for diverse energy-related applications.